PENGARUH DUKUNGAN SOSIAL, BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP STRES KERJA PERAWAT RUMAH SAKIT JIWA MUTIARA SUKMA PROVINSI NUSA TENGGARA BARAT - Lalu Erwin Musyaddat (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This research is aimed to analyze the influenced of social support, work demand and work environment toward the stressed of Nurses at Mutiara Sukma Psychiatric Hospital in West Nusa Tenggara. To collect the data by random sampling method. The population of this research is  99 nurses. Those data analyze through double regresi linier. The result showed that social support, work demand and work environment have influenced toward job stressed of Nurses at Mutiara Sukma Psychiatric Hospital in West Nusa Tenggara. Work demand has been the most influenced towards job stress of Nurses at Mutiara Sukma Psychiatric Hospital in West Nusa Tenggara. From the result of these study it is recommended to the management  of Mutiara Sukma Psychiatric Hospital in West Nusa Tenggara to facilitate and address the needs of all nurses at Mutiara Sukma Psychiatric Hospital in West Nusa Tenggara. Keywords: job stress, Social Supports, Work Demand, Work Environment